The Relationship between Germ Patterns and Severity of Diabetic Ulcers Based on Wagner's Score at Dr. M. Djamil General Hospital Padang - Gilang Dwipa Decroli; Raflis Rustam; Vendry Rivaldy (HM Publisher, 2022)
Background: Diabetes Mellitus (DM) is a condition of increasing blood sugar levels which increases the risk of macrovascular and microvascular damage, thereby reducing the quality of life of the sufferer. One of the common complications in people with diabetes mellitus is diabetic ulcers. The classification system commonly used to determine the degree of diabetic ulcers is Wagner's criteria, which consists of 5 degrees of severity. Diabetic wounds become a place for bacterial growth and the production of exudate, which results in a longer healing process and causes tissue damage. Methods: This study is a cross-sectional analytic observational study in diabetic ulcer patients treated at Dr. M. Djamil General Hospital Padang. The sampling technique in this study was consecutive sampling. The subjects of this study amounted to 36 people, with the majority aged >50 years and the female sex being found more than the male. Data analysis was performed using SPSS version 25 through univariate and bivariate analysis. Results: The grades of diabetic ulcers in the treated patients ranged from mild to severe. All subjects in this study had monomicrobial results. Gram-negative bacteria were the most commonly found, namely, 77.8%. In this study, there was no significant relationship between bacterial patterns and the severity of diabetic ulcers based on Wagner in patients treated at Dr. M Djamil General Hospital Padang (p-value > 0.05). Conclusion: Klebsiella sp is the most common type of bacteria that causes diabetic ulcers. No polymicrobial bacteria were found in this study. No correlation was found between the pattern of germs and the severity of diabetic ulcers in patients treated at Dr. M Djamil General Hospital, Padang.